Dentistry undergraduates facing dental care for patients with mental disabilities (Research, Society and Development, 2021)
The world population is growing every day and within this population there is a portion currently called people with disabilities, fits in this group those who have a disability, be it mental, sensory, physical, developmental, emotional and/or behavioral as well. as limiting conditions. Several sources indicate that there is a lack of better implementation of the discipline of care for patients with disabilities within the Faculties of Dentistry in Brazil, the absence of this discipline ends up allowing the development of fears and anxieties in academics which will be taken to their professional life, affecting the care of people with disabilities This work aims to develop an informational cluster about the dental care of people with disabilities which can serve as a source of knowledge for both students in the course of dentistry and for professionals in the area. To carry out this work, scientific articles on the subject available in online databases such as PubMed, Scielo, BVSalud, presented in Portuguese, were used as a bibliographic base. At the end of this work, it was concluded that there is an urgent need for the immediate implementation of the discipline, and extension projects for dental care for these people.